"What You See, Is What You Get?" Guidelines for Influencing Consumers' Perceptions of Consumer Durables through Product Appearance. Issue 3 (30th June 2017) - Mugge, Ruth; Dahl, Darren W.; Schoormans, Jan P. L.
Abstract : Consumers often purchase consumer durables without using these products beforehand. Product appearance is then one of the factors that consumers use to form inferences about the experience and credence attributes of consumer durables. For companies, it is important to successfully manage these inference processes of consumers to create a competitive advantage. However, a comprehensive understanding of the relationships between product appearance and the inferences about products' experience and credence attributes is lacking. This research provides empirically based, generalizable guidelines to assist companies with selecting the product appearance of consumer durables to trigger strategically valued experience and credence attributes. An empirical analysis of 120 consumer durables, belonging to four product categories on 31 design characteristics identifies five design dimensions (i.e., harmony, novelty, natural, weight, compressed) that differentiate product appearances of consumer durables. Furthermore, the findings show that these design dimensions relate to perceptions of performance quality, ease of use, and technological advancement. Specifically, product appearances that score high on harmony, neutral on novelty, and somewhat above neutral on weight trigger the most positive performance quality perceptions. Product appearances that score high on natural, low on novelty, and neutral on compressed trigger the most positive ease of use perceptions. Novel and nonnatural appearances prompt positive inferences about technological advancement. These findings are integrated into a discussion of the managerial implications and the potential avenues for future research on product appearance.